The Electrophysiological Perspectives of Essential, Enhanced Physiological, and Physiological Tremors - sabah najim, nawras; H. Ameer, Abdulnasir; A. Mohammed, Azad (Journal of the Faculty of Medicine Baghdad, 2022)
Abstract: Background: The most frequent movement issue seen in clinical practice is tremors. It is known as repetitive, involuntary oscillations. The diagnostic process for tremor patients can be time-consuming and complicated, as the identification of “Essential Tremor” and its distinction from other types of tremor.Objectives: This study aimed to describe the electrophysiological findings of essential, enhanced physiological, and physiological tremors, using surface electromyography and an accelerometer.Patients and Methods: The study included 24 patients with essential tremors, 10 patients with enhanced physiological tremors, and 10 patients with physiological tremors. We assessed the frequency, amplitude, and muscular contraction pattern of tremors during rest, posture, and a 1 kg load. Results: The tremor frequency of essential tremor patients was about 4.2-10.1 Hertz, while enhanced physiological tremor and physiological tremor were increased to 6.1–12.7 Hertz and 5.1-10.2 Hertz, respectively. The essential tremor group muscle contraction pattern was predominantly synchronous, as do all enhanced physiological, and physiological tremor patients, but with more fine low amplitude muscle bursts. By varying the tremor frequency and the weight load effect, tremor analysis could discriminate essential from enhanced physiological, and physiological tremors.Conclusions: The tremor analysis using surface electromyography and an accelerometer is sufficient to differentiate between essential tremors, enhanced physiological tremors, and physiological tremors.